Research on attack and defence control of martial arts arena robot based on kinodynamics. (16th April 2020) - Liu, Guoli; Liang, Yadong
In the research of intelligent mobile robot, autonomous mobility is a very key problem. It is very important to accurately and quickly respond to the surrounding environment, avoid obstacles in the process of moving in real time and move to the destination without interruption. Most of the existing path planning and obstacle avoidance algorithms do not consider the kinematic and geometric constraints of the robot parameters, there will be physical feasibility and versatility problems in the actual robot application; the existing martial arts challenge arena robot attack and defence control strategy, mainly rely on experience and try, accuracy and flexibility and other aspects are inadequate. In view of this, this article proposes a dynamic model based on virtual force, and applies it to the martial arts challenge arena robot, develops a set of attack and defence control strategy of martial arts challenge arena robot, completes the simulation experiment and the actual robot experiment, analyse the experimental results, and puts forward the improvement scheme. The experimental results show that the motion model proposed in this article can help the robot to complete the obstacle avoidance planning task, and the attack and defence control model based on the motion modelling can effectively improve the obstacle avoidance efficiency and attack and defence intensity of the martial arts challenge arena robot, and enhance the competitiveness of its confrontation.